Analisis Forensik Terhadap Kekerasan Benda Tajam Pada Korban Hidup - Hadytiaz, Muhammad Farhan; Achmad, Djumadi; Mathius, Denny (Universitas Pahlawan Tuanku Tambusai, 2024)
Sharp object violence on living victims is a problem that requires comprehensive medical and legal treatment. Forensic analysis of sharp object wounds plays an important role in determining the type of weapon used, the direction of the attack, and the dynamics of the incident involving the victim. This study aims to provide an in-depth understanding of the role of forensic science in analyzing sharp object wounds, with a focus on the physical and psychological aspects of the victim. The research method used is a literature review, in which various studies and case reports on sharp object violence on living victims are reviewed in depth. This approach provides a comprehensive picture of the characteristics of the wound, forensic examination methods, and the impact of physical and emotional trauma experienced by the victim. The results of this study indicate that forensic analysis of sharp object violence on living victims is very important for health aspects. Through wound examination, forensic experts can identify the type of weapon and estimate the strength and direction of the attack, which are crucial for determining the right medical treatment. Wound management must be carried out quickly to prevent complications, while attention to the psychological impact is also needed to support the holistic recovery process.